HPLC-MS/MS method for determination of betamethasone in human plasma with application to a dichorionic twin pregnancy pharmacokinetic and placental transfers studies (Brazilian Journal of Pharmaceutical Sciences, 2023)
Betamethasone (BET) is a synthetic glucocorticoid recommended for pregnant women at imminent risk of preterm birth before 34 weeks to reduce neonatal complications. There are different techniques to describe BET plasma quantification. However, none quantified the plasmatic concentration of BET in dichorionic (DC) twin pregnancies using LC-MS. Our objectives were to develop and validate a method for quantifying BET by LC-MS for pharmacokinetic (PK) and placental transfer studies in DC twin pregnancies. Blood samples were collected after intramuscular administration of a single BET dose containing 6 mg disodium phosphate + 6 mg acetate. BET was determined in plasma by liquid-liquid extraction. The method showed linearity in the range of 2-250 ng/mL, as well as precision and accuracy with a coefficient of variation and relative standard errors ≤ 15%. Additionally, the method presented selectivity and did not present matrix or carry-over effect. Stability tests also presented coefficient of variation and relative standard errors ≤ 15%. This is the first study which describe maternal and fetal plasma concentrations of BET in a DC twin pregnancy. The BET PK parameters were AUC0-∞, CL/F, Vd/F, Cmax, Tmax of 292.20 h*ng/mL, 39.08 L/h, 278.72 L, 25.55 ng/mL and 0.58 h, respectively. The placental transfer ratios of umbilical vein/maternal vein and intervillous space/maternal vein were 0.14 and 0.19 and 0.40 and 0.27 for both twins, respectively. However, a clinical study with more subjects is imperative to confirm this higher concentration of BET in the intervillous space.